Visual programming tools for parallel processing - Tan, Hung Khoon. (2009)
With the increased complexity of applications, parallel computing has proved to be an alternative to supercomputing in solving large problems. Although the performance and cost-performance benefits of parallel systems are attractive, the difficulties in pro-gramming have been a major hindrance in greater acceptance.